Devices for express diagnostics of power semiconductor devices and semiconductor converters - E. B. Koroleva; S. M. Kurmashev; K. K. Kim; A. A. Tkachuk; A. A. Kuznetsov (Омский научный вестник)
The increase in the power of power semiconductor converters operated in the railway industry is associated with the use of group connections of power semiconductor devices in them, the variation in the parameters of which, and, therefore, their unequal load, causes a decrease in the reliability of the power semiconductor converters as a whole. In this regard, it becomes necessary to develop and implement innovative methods and devices for express diagnostics in order to identify potentially unreliable semiconductor devices, and the implementation of technical diagnostics should not be associated with dismantling the electrical circuits of the converters. The method is proposed for determining potentially unreliable power semiconductor devices in group connections based on the results of analyzing the distribution of reverse currents in parallel branches, which made it possible to create a series of devices for diagnosing power semiconductor devices in converters, both with and without communication resistors. The methodological error of measurements made using the developed express diagnostics devices of the transducers do not exceed the standard value equal to 10 %.